2019
DOI: 10.1002/pros.23780
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for inhibition of non‐adrenergic prostate smooth muscle contraction by pharmacologic intervention

Abstract: Background Inhibition of prostate smooth muscle contraction by α1‐adrenoceptor antagonists (α1‐blockers) is a first‐line medical treatment of lower urinary tract symptoms suggestive of benign prostatic hyperplasia. Increased smooth muscle tone in the hyperplastic prostate may drive urethral obstruction, resulting in bladder outlet obstruction and voiding symptoms. However, efficacy of α1‐blockers is limited, as non‐adrenergic mediators including endothelin‐1 and thromboxane A2 (TXA2) increase prostate smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…While the role of RhoA for promotion of smooth muscle contraction is well established for all smooth muscle tissues (Somlyo and Somlyo, 2000;Somlyo and Somlyo, 2003;Christ and Andersson, 2007;Puetz et al, 2009), a similar role for RacGTPases has been proposed more recently. NSC23766 and EHT1864 inhibited contractions of human prostate tissues, so that a procontractile role of Rac1 has been proposed for prostate smooth muscle (Wang et al, 2015;Yu et al, 2019). These previous and our present findings for the detrusor and prostate are in line with other studies, where Rac inhibitors inhibited cholinergic, serotonin-, and endothelin-induced contractions of airway tissues from humans, mice and rats, as well as adrenergic and serotonin-induced contractions of rodent vessels, and contractions of the mouse ileum (Staiculescu et al, 2013;Rahman et al, 2014;Shibata et al, 2015;Andre-Gregoire et al, 2017;Harvey et al, 2017;Sakai et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While the role of RhoA for promotion of smooth muscle contraction is well established for all smooth muscle tissues (Somlyo and Somlyo, 2000;Somlyo and Somlyo, 2003;Christ and Andersson, 2007;Puetz et al, 2009), a similar role for RacGTPases has been proposed more recently. NSC23766 and EHT1864 inhibited contractions of human prostate tissues, so that a procontractile role of Rac1 has been proposed for prostate smooth muscle (Wang et al, 2015;Yu et al, 2019). These previous and our present findings for the detrusor and prostate are in line with other studies, where Rac inhibitors inhibited cholinergic, serotonin-, and endothelin-induced contractions of airway tissues from humans, mice and rats, as well as adrenergic and serotonin-induced contractions of rodent vessels, and contractions of the mouse ileum (Staiculescu et al, 2013;Rahman et al, 2014;Shibata et al, 2015;Andre-Gregoire et al, 2017;Harvey et al, 2017;Sakai et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…For the prostate, cytotoxic effects of NSC23766 and EHT1864 were recently excluded to account for contraction inhibition in organ bath experiments, as these effects did not occur quickly enough (Yu et al, 2019). As very similar conditions were applied here to bladder tissues, it appears unlikely, that cytotoxic effects underly the inhibitory effect on detrusor contraction in our study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recent studies have also demonstrated the potential of NSC23766 in combination therapy to overcome resistance to targeted as well as cytotoxic therapies (Karpel-Massler et al, 2017;Tian et al, 2018). Nonetheless, although the use of NSC23766 may look promising in some instances, the high effective concentrations (µM range) and the reported off-target effects in platelets, on alfa-1-adrenergic receptors and CXCR4 chemokine receptors, limits its therapeutic use (Dutting et al, 2015;Mills et al, 2018;Yu et al, 2019).…”
Section: Targeting Tiam1mentioning
confidence: 99%